2021
DOI: 10.4081/jphr.2021.2046
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Treatment Outcome and Associated Factors among Tuberculosis Patients at Wolayta Sodo Teaching and Referral Hospital, Southern Ethiopia: A Retrospective Study

Abstract: Background: Tuberculosis is a major public health problem throughout the world particularly in resource limited countries. Measuring and reporting of TB treatment outcomes and identifying associated factors are fundamental part of TB treatment. The aim of this study was to assess TB treatment outcome and associated factors among TB patients in Wolayta Sodo Teaching and Referral Hospital, Southern Ethiopia.Design and Methods: Facility based retrospective cohort study was conducted in Wolayta Sodo Teaching and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
18
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 20 publications
11
18
4
Order By: Relevance
“…In contrast to this study, previous studies reported that males were dominant, such as a study in Dessie [9], Goba [10], and Harar [11]. Te burden of TB was higher among the age groups of 15-29 and 30-44 years, with 28.4% and 31.7%, respectively, which was in agreement with the previous study in southern Ethiopia [13]. Tis might be indicating a negative infuence of TB on the socioeconomic state of society, particularly in lowincome countries.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to this study, previous studies reported that males were dominant, such as a study in Dessie [9], Goba [10], and Harar [11]. Te burden of TB was higher among the age groups of 15-29 and 30-44 years, with 28.4% and 31.7%, respectively, which was in agreement with the previous study in southern Ethiopia [13]. Tis might be indicating a negative infuence of TB on the socioeconomic state of society, particularly in lowincome countries.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, sex was marginally associated with poor TB treatment outcomes where males were two times more likely to had poor TB treatment outcomes than females. This finding was in agreement with previous similar studies conducted elsewhere [1,11,15,27]. This might be due to a relatively higher exposure of males to cigarette smoking, traveling a long distance for economic reasons and alcohol consumption as compared to females.…”
Section: Plos Global Public Healthsupporting
confidence: 93%
“…The level of poor TB treatment outcomes observed in this study was 14.5%. This was comparable to findings from similar studies in southern Ethiopia, 14.8% in Dilla Town [14], and PLOS GLOBAL PUBLIC HEALTH 17.5% in Wolayta Sodo [15]. A systematic review and meta-analysis on TB treatment outcomes in Ethiopia that included studies published between 2003 and 2016 reported a 16.3% poor TB treatment outcome at a national level [9].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A study conducted from a teaching and referral hospital in Wolayta Sodo, Ethiopia, reported similar findings. 39 However, studies in Ethiopia and abroad reported that undernutrition, 31 , 33 HIV infection, 21 , 26 and history of anti-TB drug use 40 were risk factors for unsuccessful treatment outcomes such as treatment failure and death. In the present study, there were a considerable number of patients with unknown HIV and BMI status, which may have underestimated the frequency of HIV infection and BMI, respectively.…”
Section: Discussionmentioning
confidence: 99%